Sonographic diagnostics, prevalence and age-based dynamics of the manifestation of prostate gland pathologies in dogs - V. R. Serhiienko; S. V. Naumenko; V. I. Koshevoy (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
Modern requirements for the welfare of domestic animals are focused not only on compliance with the requirements of maintenance, feeding, but also on ensuring a long active life of animals, especially older ones – 8–10 years and more. The problems that practical veterinary andrology constantly faces are due to the age factor, hormonal and metabolic changes and quite often, a long-term lack of sexual use of males, which lead to the occurrence of reproductive pathologies, including – the prostate gland. The main among these pathologies are the development of hyperplasia, inflammatory processes and neoplasms – all of them cause discomfort in animals and can significantly worsen the quality of life. Therefore, monitoring the condition of the prostate in dogs, especially older ones, is an urgent task. At the same time, it is important to establish the dynamics of the manifestation of prostate diseases and develop diagnostic and differential criteria. This can be done with the help of modern ultrasound scanners, the regular use of which for the diagnosis of sexual pathologies in males is a perfect tool used all over the world. Therefore, the purpose of this work was to conduct sonographic diagnostics of the prostate in dogs, whose owners turned to private veterinary clinics in the city of Kharkiv in 2022–2024. to establish diagnostic and differential signs, forms of manifestation, prevalence of prostate pathologies depending on the age of the male. The key characteristics of prostate scanograms in normal, with prostatitis, hyper- and neoplasia, cystic lesions were determined. It was shown that in dogs aged 7–9 years, prostate pathologies were detected in 41.2 % of the total number of examined animals (in particular, prostatitis in 38.2 %, including acute form in 14.7 %, and chronic – in 23.5 % of dogs). In older males (10 years and older), pathological changes in the prostate were diagnosed in 81.3 % of the number of examined animals, with chronic prostatitis being the most common in them (84.6 % of the number of animals with prostate pathology). On the contrary, in younger dogs, pathological processes in the prostate gland were rarely visualized. Thus, further research by the authors of the article will be aimed at developing an effective means of treating prostatitis in dogs, as a significant component of the structure of prostate diseases.